The Rule of Law as the Lodestar of the European Convention on Human Rights: The Strasbourg Court and the Independence of the Judiciary - Spano, Robert (Teisė, 2021)
The rule of law is a principle of constitutional importance under the European Convention on Human Rights. For decades, it has guided the work of the Strasbourg Court. The article discusses the principle’s ideological core as a fundamental component of “European public order” and its three normative dimensions, as they find their expression in the case-law of the Court. The author then discusses in detail the rule of law’s most important structural principle under the Convention, the independence of the judiciary.
Keywords: European Court of Human Rights; rule of law; judicial independence; European public order